The efficacy and safety of Chinese herbal medicine as an add-on therapy for amyotrophic lateral sclerosis: An updated systematic review and meta-analysis of randomized controlled trials - Liao, Yingdi; He, Sijin; Liu, Duo; Gu, Lihua; Chen, Qigang; Yang, Shuang; Li, Daiying (Frontiers in Neurology, 2022)
Background: Amyotrophic lateral sclerosis (ALS) has attracted widespread attention due to its unknown pathogenesis, rapid progression, life-threatening and incurable characteristic. A series of complementary therapy such as Chinese herbal medicine (CHM) are available in clinical and also have been studied recently. However, it is unclear whether add-on CHM to relieve disease symptom or to extend life span, so we conducted this updated meta-analysis to validate the efficacy and safety. Methods：Six electronic databases were searched for randomized controlled trials of CHM for ALS that were published up to April 2022. Two researchers independently screened the literature, assessed the risk of bias for each trial, and extracted data. The methodological quality of the included trials was assessed using the Cochrane risk of bias tool. Pooled data analysis was performed using RevMan 5.3. Results: A total of 14 trials published 15 articles with 1141 participants were included in the systematic review. In terms of ALSFRS, CHM was superior to placebo at the end of treatment of three months(MD=0.70, 95%CI 0.43 to 0.98, P<0.01) and riluzole at the end of treatment of four weeks (MD=2.87, 95%CI 0.81 to 4.93, P<0.05), and was superior to conventional medicine(CM) alone when used as an add-on therapy at the end of treatment of eight weeks (MD=3.5, 95%CI 0.51 to 6.49, P<0.05). In terms of m-Norris,the changed score from baseline to the end of treatment of more than three months was significantly different between CHM plus CM group and CM alone group(MD=2.09, 95%CI 0.62 to 3.55, P<0.01). In addition, CHM had a better effect on increasing clinical effective rate(RR=1.54, 95%CI 1.23 to 1.92,, P<0.01 and improving forced vital capacity (MD=7.26, 95%CI 2.92 to 11.60, P<0.01). However, there was no significant difference between CHM therapy and CM on improving life quality(MD=5.13, 95%CI -7.04 to 17.31, P=0.41) and decreasing mortality(RR=0.41, 95%CI 0.04 to 4.21, P=0.46). Conclusion: Our study suggests that short term adjunct use of CHM could improve ALSFRS score and clinical effect with a good safety profile, when compared with placebo or riluzole alone. But future research or clinic should be centered in long-term efficacy of patient-oriented outcomes.